Hubungan Kekuatan Otot Lengan Dan Kelincahan Terhadap Kemampuan Tangkapan Dua Kaki Mahasiswa STKIP YPUP Makassar - Akbar Yusuf; Tri Anggriawan; Febri Hamsah (Gerak: Journal of Physical Education, Sports, and Health, 2021)
This study aims to obtain answers to problems (1) Is there a significant relationship between arm muscle strength and the ability to catch two legs in the wrestling sport of STKIP YPUP Makassar students?. (2). Is there a significant relationship between agility and the ability to catch two legs in the wrestling sport of STKIP YPUP Makassar students? two independent variables and one dependent variable.The population and the sample are students of STKIP YPUP Makassar chosen by random sampling obtained as many as 20 people.The data analysis technique used is single correlation analysis and multiple correlation using computer facilities through the SPSS program. Based on the results of data analysis, it can be concluded as follows: (1) there is a significant relationship between arm muscle strength and the ability to catch two legs in the wrestling sport of STKIP YPUP Makassar students with a value of r = 0.753 (P <0.05), (2) there is a significant relationship with agility. on the ability to catch two legs in the wrestling branch of STKIP YPUP Makassar students with a value of r = 0.754 (P <0.05), (3) there is a significant relationship between arm muscle strength and agility on the ability to catch two legs in the wrestling sport of STKIP YPUP Makassar students with a value of R = 0.821 (P<0.05).